Modeling two-qubit Grover's algorithm implementation in a linear optical chip - Samsonov, E; Kiselev, F; Shmelev, Y; Egorov, V; Goncharov, R; Santev, A; Pervushin, B; Gleim, A (Physica scripta, 2020)
This paper introduces a model of Grover's algorithm suitable for implementation in a linear photonic chip. We compare two known realizations of its main components, two-qubit CZ gates, in order to define optimal chip architecture. The algorithm operation is simulated considering directional coupler imperfection influence on the scheme parameters. We also determined tolerance boundaries for distortions of the coupler dimensions.